Spolne razlike v formalnem in neformalnem delu - Černigoj-Sadar, Nevenka (Družboslovne razprave, 2000)
The purpose of the study is to explore the macro and micro level influences on the production and reproduction of gender differences in formal and informal work. The position of men and women on the labour market in Slovenia and EU is discussed on the basis of a critical analysis of various types of welfare systems and gender division of labour. The empirical part of the studyis based on a secondary analysis of statistical data, the Slovenian public opinion polls in the nineties and on the Quality of Life 1994 database.
Keywords: družina; family; delitev dela; spolna neenakost; spolna diferenciacija; spolna diskriminacija